Effects of neoclassical toroidal viscosity on toroidal rotation under electron cyclotron resonance heating on J-TEXT tokamak - Hanhui Li; Youwen Sun; Lu Wang; Xingting Yan; Hui Sheng; Zhoujun Yang; Li Gao; Yonghua Ding; Zhongyong Chen; Zhipeng Chen; Donghui Xia; Wei Yan; et al. (Nuclear Fusion)
Influence of neoclassical toroidal viscosity (NTV) torque on intrinsic toroidal rotation caused by internal kink mode (IKM) in the J-TEXT tokamak is studied. It is observed that the toroidal rotation in the counter-current direction decreases after the on-axis electron cyclotron resonance heating (ECRH) is turned on, during which the IKM is strongly enhanced. The change of plasma rotation due to ECRH decreases with increasing plasma density, which is due to a decreasing of the IKM’s amplitude. This gives direct evidence that the change in intrinsic rotation strongly depends on the amplitude of the IKM. It is shown in the modeling that the decrease in the amplitude of the IKM reduces the NTV torque, and hence the influence on the toroidal rotation becomes weaker. The modeled dependence of rotation variation on plasma density agrees well with the observations. These results indicate that the NTV torque caused by the IKM plays a key role in changing the intrinsic core toroidal rotation in ECRH plasmas in the J-TEXT tokamak.